Money Laundering As One Of The Risks Lurking Behind Documentary Credit Contract (Latakia University Journal - Economic and Legal Sciences Series, 2021)
With the emergence of globalization as a new epoch in World Order, there has been an increase in the commercial and industrial activities as well as in economic freedom. The inclination to liberate both domestic and foreign trades has particularly grown due to the important role they play in terms  of developing local economies and world economy as well. This has been achieved through using different means, the most important of which is documentary credit contract. This process has been facilitated by the huge improvements in the fields of technology and communications accompanied by the smooth transfer of capitals throughout the world. On the other hand, this epoch has given birth to new types of crime. The most important one is arguably money laundering, which is regarded as one of the most dangerous economic crimes threatening World's security not to mention its devastating effects on world economies. This is why money laundering has become the main subject of study and discussion in local, regional and, international assemblies interested in trans-border crime, which have confirmed the necessity of combating this phenomenon and dealing with it as an international problem.Hence, it can be argued that this issue has positive and negative sides : documentary credit and the potential risk of using it embodied in money laundering. The two sides exist side by side in banks, which are esteemed to play an important, leading role in managing a country's economy and constitute one of the main parties of documentary credit and the most fertile environment for money laundering.